miR482f and miR482c-5p from edible plant-derived foods inhibit the expression of pro-inflammatory genes in human THP-1 macrophages - Díez-Sainz, Ester; Lorente-Cebrián, Silvia; Aranaz, Paula; Amri, Ez-Zoubir; Riezu-Boj, José I.; Milagro, Fermín I. (Frontiers in Nutrition, 2023)
Edible plants can exert anti-inflammatory activities in humans, being potentially useful in the treatment of inflammatory diseases. Plant-derived microRNAs have emerged as cross-kingdom gene expression regulators and could act as bioactive molecules involved in the beneficial effects of some edible plants. We investigated the role of edible plant-derived microRNAs in the modulation of pro-inflammatory human genes. The results revealed that miR482f and miR482c-5p are present in several edible plant-derived foods, such as fruits, vegetables, and cooked legumes and cereals, and fats and oils. Transfections with miR482f and miR482c-5p mimics decreased the gene expression of CLEC7A and NFAM1, and TRL6, respectively, in human THP-1 monocytes differentiated to macrophages, which had an impact on gene expression profile of inflammatory biomarkers. Both microRNAs (miR482f and miR482c-5p) resisted degradation during digestion and were detected in human feces, although not in serum. In conclusion, our findings suggest that miR482f and miR482c-5p can promote an anti-inflammatory gene expression profile in human macrophages in vitro and their bioavailability in humans can be achieved through diet, but eventually restricted at the gut level.